Comparative Antibacterial Study of Silver Nanoparticles Doped Activated Carbon Prepared by Different Methods - Pandey, Pragya; Karki, Bivek; Lekhak, Binod; Koirala, Agni R.; Sharma, R. K.; Pant, Hem R. (Journal of the Institute of Engineering, 2020)
Activated carbon is greatly used to adsorb toxic heavy metals from water bodies. Simultaneous removal of such pollutants and pathogenic impurities is essential for safe drinking water. In this study, silver nanoparticles (NPs) doped activated carbon (AC) composite was fabricated via hydrothermal technique and green synthesis technique using commercial activated carbon powder and silver nitrate solution. Several analytical techniques, including scanning electron microscopy (SEM), energy dispersive x-ray (EDX), X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed the formation of silver nanoparticles on the surface and pores of AC. The prepared composite materials were accessed for their anti-bacterial property using Escherichia coli and Staphylococcus aureus and found that such materials have good antibacterial activity which shows that as fabricated composite can be used potentially for water treatment.